In-search of Trainee’ Performance Drivers: Evidence from Internship Training Program for Indonesian Vocational Teachers - Halim, Nana; Dwirosanti, Nining; Wonodhipo, Arief; Irwan, Wawan Saepul (Politeknik Negeri Bandung, 2024)
This study investigates the drivers of trainee performance in upskilling/reskilling training program through an internship for vocational high school teachers. Data was gathered from 652 high school business and tourism teachers nationwide who had completed an internship program managed by BISPAR, Indonesia. The data, analyzed using SEM-PLS, results in two important findings. First, training inputs, covering trainee characteristics, training design, and work environment, are important determinants of trainees’ experience in the internship program. Among these factors, statistical results reveal that training design is the key to trainee reaction and learning during the training. Second, the total effect analysis shows that teachers’ behavior in transferring new competency acquired from the training is greatly influenced by the school’s environment factors. The managerial implication of these findings is thoroughly discussed.